2010
DOI: 10.1016/j.cell.2009.12.041
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase Sirt6 Regulates Glucose Homeostasis via Hif1α

Abstract: Summary SIRT6 is a member of a highly conserved family of NAD+-dependent deacetylases with various roles in metabolism, stress resistance and lifespan. SIRT6 deficient mice develop normally but succumb to a lethal hypoglycemia early in life; however, the mechanism underlying this hypoglycemia remained unclear. Here, we demonstrate that SIRT6 functions as a histone H3K9 deacetylase to control the expression of multiple glycolytic genes. Specifically, SIRT6 appears to function as a co-repressor of the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
915
4
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 904 publications
(960 citation statements)
references
References 51 publications
38
915
4
3
Order By: Relevance
“…Understanding the role of Sirtuins in aging stem cells will likely provide insights into the mechanisms that regulate stem cell homeostasis, particularly in response to stress stimuli. In addition, the ability of Sirtuins to regulate both organismal energy metabolism (Banks et al, 2008;Feige et al, 2008;Kim et al, 2010;Ramadori et al, 2010;Zhong et al, 2010) and chromatin may be particularly important for the response of adult stem cells to environmental stimuli such as dietary restriction that are known to promote longevity and delay signs of aging.…”
Section: Histone Acetylation In Aging Stem Cellsmentioning
confidence: 99%
“…Understanding the role of Sirtuins in aging stem cells will likely provide insights into the mechanisms that regulate stem cell homeostasis, particularly in response to stress stimuli. In addition, the ability of Sirtuins to regulate both organismal energy metabolism (Banks et al, 2008;Feige et al, 2008;Kim et al, 2010;Ramadori et al, 2010;Zhong et al, 2010) and chromatin may be particularly important for the response of adult stem cells to environmental stimuli such as dietary restriction that are known to promote longevity and delay signs of aging.…”
Section: Histone Acetylation In Aging Stem Cellsmentioning
confidence: 99%
“…SIRT3, 4, and 5 regulate ATP production, metabolism, apoptosis, and cell signaling (Haigis et al, 2006;Michishita et al, 2005;Onyango et al, 2002;Schwer et al, 2002). SIRT6 is involved in genomic DNA stability and repair, and crucial in metabolism and aging Zhong et al, 2010). No robust activity has been found for SIRT7 as of yet (Table 1).…”
Section: Overview Of Sirtuinsmentioning
confidence: 99%
“…SIRT6 is likely linked to cellular metabolism and aging. A study of mice with a targeted deletion of SIRT6 showed that SIRT6 is essential for survival and controls glucose homeostasis through HIF-1α (Mostosalvsky et al, 2006;Zhong et al, 2010). SIRT6 interacts with NF-κB and deacetylates histone H3 lysine 9 (H3K9) at NF-κB target gene promoters leading to inactivation of many of the same transcriptional programs observed in aged tissues, including genes controlled by NF-κB (Kawahara et al, 2009).…”
Section: Sirt6mentioning
confidence: 99%
“…As a mono-ADP-ribosyltransferase, SIRT6 uses NAD + as a cosubstrate to transfer the 32 P-label from NAD + to mSIRT6 and histones [4-6]. SIRT6 harbors low-level deacetylase activity for NAD + -dependent deacetylation of non-histone proteins [7] and linking site-specific histones [8][9][10][11].SIRT6 is present in all eukaryotes including mammals [12], and deacetylates histone H3 lysine 9 (H3K9) and histone H3 lysine K56 (H3K56) to maintain dynamic changes in their acetylation levels at the telomeres over cell cycles. Histone deacetylation modifies the telomeric chromatin by preventing chromosomal fusion at the end of telomeres, and negatively regulates ageing-correlated gene-expression programs depending on nuclear factor-B [8,9,13].…”
mentioning
confidence: 99%
“…As a mono-ADP-ribosyltransferase, SIRT6 uses NAD + as a cosubstrate to transfer the 32 P-label from NAD + to mSIRT6 and histones [4-6]. SIRT6 harbors low-level deacetylase activity for NAD + -dependent deacetylation of non-histone proteins [7] and linking site-specific histones [8][9][10][11].…”
mentioning
confidence: 99%